Supratotal Resection of Gliomas With Awake Brain Mapping: Maximal Tumor Resection Preserving Motor, Language, and Neurocognitive Functions - Motomura, Kazuya; Ohka, Fumiharu; Aoki, Kosuke; Saito, Ryuta (Frontiers in Neurology, 2022)
Gliomas are a category of infiltrating glial neoplasms that are often located within or near the eloquent areas involved in motor, language, and neurocognitive functions. Surgical resection being the first-line treatment for gliomas, plays a crucial role in patient outcome. The role of the extent of resection (EOR) was evaluated, and we reported significant correlations between a higher EOR and better clinical prognosis of gliomas. However, recurrence is inevitable, even after aggressive tumor removal. Thus, efforts have been made to achieve extended tumor resection beyond contrast-enhanced mass lesions in magnetic resonance imaging (MRI)-defined areas, a process known as supratotal resection. Since it has been reported that tumor cells invade beyond regions visible as abnormal areas on MRI, imaging underestimates the true spatial extent of tumors. Furthermore, tumor cells have the potential to spread 10–20 mm away from the MRI-verified tumor boundary. The primary goal of supratotal resection is to maximize EOR and prolong the progression-free and overall survival of patients with gliomas. The available data, as well as our own work, clearly show that supratotal resection of gliomas is a feasible technique that has improved with the aid of awake functional mapping using intraoperative direct electrical stimulation. Awake brain mapping has enabled neurosurgeons achieve supratotal resection with favorable motor, language, and neurocognitive outcomes, ensuring a better quality of life in patients with gliomas.